Efecto de la fertilización nitrogenada e intervalos de corte sobre el valor nutritivo potencial del pasto King grass (Pennisetum purpureum x Pennisetum typhoides). Durante la época lluviosa (ING) - Fallas, Edgar; Arroyo, Rafael; Eduarte, Eduardo; Villalobos, Leonidas; Mojica, Fernando; Aguirre, Diego (Uniciencia, 1987)
Data from a experiment that utilized King Grass forage (Pennisetum purpureum x Pennisetum typhoides) with four nitrogen fertilization levels (0, 100, 200 and 300 kg Ha-1) and five harvest intervals (35, 49, 63, 77 and 91 d) were analyzed by an analysis of variance under an split plot design. The study variables were dry matter production (DM kg Ha-1 harvest-1), crude protein production (CP kg Ha-1 harvest-1) and its CP% contents and in vitro dry matter digestibility (I.V.D.M.D). The research was done in National University, Santa Lucía Research Farms at Heredia, Costa Rica. The climatic characteristics during the research period were 19.7°C temperature and 2.000 mm rainfall mean.Dry matter production was increased by the nitrogen fertilization (P=